Komisja Kodyfikacyjna II RP: pozycja ustrojowa, struktura organizacyjna, podejmowanie decyzji - Górnicki, Leonard (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Established one hundred years ago, the Codification Commission of the Second Polish Republic initiated and prepared draft legislation dealing with private, criminal, substantive and procedural law as well as the judiciary and the legal profession. The Commission served as de facto legislator, that is lawmaker in the sociological sense, for it had a genuine impact on the content and form of legislative acts.In the article the author analyses the position of the Codification Commission of the Second Polish Republic within the legal system, on which opinions differ in the literature on the subject. He defends the thesis that is was a central state institution, the existence of which was not, however, coordinated with the political system of the Second Polish Republic. Next, he investigates the impact of the transformations of the organisational structure and decision-making methodology on the efficiency of the Commission’s codification process. He takes into account the management and administration of the Codification Commission, organisation of work in Departments, Sections Subsections, Subcommittees, role of the delegates of the Minister of Justice and delegates of ministries, finally — decision-making mechanisms, including adoption of drafts as well as work in the Sections Subsections and Subcommittees.The author concludes that the experiences of the Second Polish Republic’s Codification Commission, a central state institution of advisory nature, established for an indefinite period, demonstrate that the best solution is to entrust codification to a special, apolitical and expert codification commission, operating with a degree of independence, of internal autonomy. Within such a commission a more effective mode of operation is preparation of drafts by teams of several people and then consultation of these drafts by larger bodies.
Keywords: Komisja Kodyfikacyjna II Rzeczypospolitej Polskiej; mechanizmy decyzyjne; efektywność procesu kodyfikacji